Magnesium-based material surface self-healing protective coating as well as preparation method and application thereof
By forming an LDH coating with co-intercalation layer of organic and inorganic corrosion inhibitors on the surface of magnesium-based materials, the problems of insufficient corrosion resistance and lack of self-repair ability of magnesium-based materials are solved, and efficient and economical long-term protection is achieved, and it is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411788986.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Due to insufficient corrosion resistance of magnesium-based materials, existing physical protection measures have significantly reduced their protective performance after the material is scratched, impacted or long-term environmental corrosion, and lacks self-repair capabilities, which require manual maintenance.
A layered bimetallic hydroxide (LDH) coating is used to co-intercalate organic corrosion inhibitors and inorganic corrosion inhibitors to form a self-healing protective coating on the surface of magnesium-based materials through hydrothermal reaction.
The preparation of self-healing protective coating on the surface of magnesium-based materials is realized, which enhances the corrosion resistance of the material, reduces maintenance costs, improves the reliability of the material, and is suitable for medical and industrial fields.
Smart Images

Figure CN119640249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface coatings, and in particular relates to a self-healing protective coating on the surface of a magnesium-based material, and a preparation method and application thereof. Background Art
[0002] Compared with traditional medical stainless steel, titanium and other metal materials, magnesium and its alloys have gradually become a research hotspot due to their biodegradability, and have great potential application prospects in the fields of temporary medical implants such as fracture internal fixation devices, guided bone regeneration membranes, and vascular stents. As a green engineering material in the 21st century, magnesium alloys are also widely used in many fields such as aerospace, automobile manufacturing, and electronic information due to their light weight, high strength and excellent mechanical properties. However, magnesium-based materials themselves are prone to corrosion, and their corrosion resistance is not enough to meet the requirements of long-term use, which has become the main bottleneck of their application. In response to this problem, existing research focuses on various physical protection methods, including traditional organic coatings such as paints and coatings, as well as inorganic and metal coatings such as anodizing, chemical conversion and electroplating. Although these methods can provide a certain degree of protection in the initial stage, their protective performance is greatly reduced after the material is scratched, impacted or corroded by the environment for a long time. These physical protection methods often lack self-repairing ability. Once damaged, they lose their protective effectiveness and require regular maintenance and recoating by humans, which not only increases costs, but also reduces the service life and reliability of the material.
[0003] In this context, the research on self-healing coatings has gradually become a new trend in the field of material protection. Self-healing coatings use special designs to automatically release repair substances when micro damage occurs, restoring the integrity and protective function of the coating. Layered double hydroxide (LDH) has a special layered structure and unique interlayer ion exchange capacity, providing an excellent carrier for the loading of corrosion inhibitors. For example, WO3 2- , VO4 3- 、MoO4 2- and PO4 3- Inorganic ions such as ions are loaded between the LDH coating layers. Although the intercalated corrosion inhibitor improves the corrosion protection performance of the LDH coating, the corrosion inhibition effect of the single corrosion inhibitor intercalated LDH coating is limited and has limitations in practical applications. At the same time, the intercalated inorganic slow-release agent ions often have potential cytotoxicity or even carcinogenicity, and their application in the biomedical field is still difficult to promote. Summary of the invention
[0004] The purpose of the present invention is to provide a self-healing protective coating on the surface of a magnesium-based material and a preparation method thereof in view of the deficiencies in the prior art.
[0005] The present invention also aims to provide the use of the self-healing protective coating on the surface of the magnesium-based material in the preparation of corrosion protection materials or biocompatible materials.
[0006] The first object of the present invention can be achieved by the following technical solution: A method for preparing a self-healing protective coating on the surface of a magnesium-based material, comprising the following steps:
[0007] (1) Surface pretreatment of magnesium-based materials;
[0008] (2) Preparation of LDH coating with organic corrosion inhibitor intercalation:
[0009] Under a protective atmosphere, preparing an aqueous solution of a divalent metal ion salt, a trivalent metal ion salt and an organic corrosion inhibitor, and adjusting the pH to obtain a reaction solution;
[0010] The magnesium-based material pretreated in step (1) and the reaction solution are placed in a hydrothermal reaction vessel to perform a hydrothermal reaction, thereby obtaining an organic corrosion inhibitor intercalated LDH coating on the surface of the magnesium-based material;
[0011] (3) Preparation of LDH coating with co-intercalation of organic and inorganic corrosion inhibitors:
[0012] Preparing an aqueous solution of an inorganic corrosion inhibitor;
[0013] The magnesium-based material with the LDH coating intercalated with an organic corrosion inhibitor obtained in step (2) is immersed in the aqueous solution of the inorganic corrosion inhibitor to carry out an ion exchange reaction, thereby obtaining an LDH self-healing protective coating intercalated with an organic corrosion inhibitor and an inorganic corrosion inhibitor on the surface of the magnesium-based material.
[0014] In the method for preparing the self-healing protective coating on the surface of the magnesium-based material:
[0015] Preferably, the magnesium-based material described in step (1) is magnesium, a magnesium alloy, a porous material containing magnesium, a porous material containing a magnesium alloy, a material surface-treated with magnesium, a material surface-treated with a magnesium alloy, a material surface-treated with a magnesium porous material, or a material surface-treated with a magnesium alloy porous material.
[0016] More preferably, the magnesium-based material in step (1) is magnesium or a magnesium alloy.
[0017] Preferably, the surface pretreatment of the magnesium-based material in step (1) comprises: grinding the magnesium-based material to remove surface oxides and impurities, and then cleaning and drying it.
[0018] Preferably, anhydrous ethanol and / or acetone may be used for cleaning, more preferably, anhydrous ethanol is used for cleaning.
[0019] Preferably, the divalent metal ion salt in step (2) is one or more of magnesium nitrate, zinc nitrate and copper nitrate.
[0020] Preferably, the concentration of the divalent metal ion salt in step (2) is 30 to 120 mmol / L.
[0021] More preferably, the concentration of the divalent metal ion salt in step (2) is 40 to 90 mmol / L.
[0022] Preferably, the trivalent metal ion salt in step (2) is one or both of aluminum nitrate and iron nitrate.
[0023] Preferably, the concentration of the trivalent metal ion salt in step (2) is 10 to 40 mmol / L.
[0024] More preferably, the concentration of the trivalent metal ion salt in step (2) is 13 to 30 mmol / L.
[0025] Preferably, the organic corrosion inhibitor in step (2) is one or more of aspartic acid, sodium aspartate and potassium aspartate.
[0026] Compared with glutamic acid, the stability of the complex formed by ASP and magnesium ions in the present invention is better than the stability of the complex formed by glutamic acid and magnesium ions, so ASP ion intercalation can give the LDH coating on the surface of the magnesium-based material a stronger self-repairing ability.
[0027] Preferably, the concentration of the organic corrosion inhibitor in step (2) is 0.6 to 30 mmol / L.
[0028] More preferably, the concentration of the organic corrosion inhibitor in step (2) is 1.5 to 20 mmol / L.
[0029] Preferably, the protective atmosphere in step (2) is one or more of nitrogen, argon and helium.
[0030] Preferably, in step (2), the pH is adjusted to 9-13.
[0031] More preferably, in step (2), the pH is adjusted to 10-12.
[0032] Preferably, the temperature of the hydrothermal reaction in step (2) is 100 to 160° C., and the time is 1 to 30 hours.
[0033] More preferably, the temperature of the hydrothermal reaction in step (2) is 110 to 140° C., and the time is 3 to 24 hours.
[0034] Preferably, the inorganic corrosion inhibitor in step (3) is sodium silicate, and the concentration of the inorganic corrosion inhibitor aqueous solution is 15 to 150 mmol / L.
[0035] More preferably, the concentration of the inorganic corrosion inhibitor aqueous solution is 25 to 120 mmol / L.
[0036] Preferably, the temperature during the ion exchange reaction in step (3) is 50 to 100° C. and the time is 1 to 10 hours.
[0037] More preferably, the temperature during the ion exchange reaction in step (3) is 60 to 90° C. and the time is 2 to 6 hours.
[0038] The present invention also provides a self-healing protective coating on the surface of a magnesium-based material, which is prepared by the above method.
[0039] The magnesium-based material surface protective coating of the present invention is mainly composed of layered bimetallic hydroxides (LDH) co-intercalated with organic corrosion inhibitors and inorganic corrosion inhibitors, which are crystallized on the surface of the magnesium-based material.
[0040] The last object of the present invention can be achieved by the following technical solution: application of the self-healing protective coating on the surface of the magnesium-based material in the preparation of corrosion protection materials or biocompatible materials.
[0041] The protective coating in the present invention can be used to protect metal materials and slow down the corrosion of metal materials. There are many types of anti-corrosion coatings. Compared with the simple LDH in the prior art, which relies on physical barrier effect to achieve protection, if the coating is partially damaged and the substrate is exposed, the substrate will dissolve rapidly. On the one hand, the ASP and silicate ion intercalated LDH in the present invention rely on the physical barrier effect of LDH itself to achieve protection; on the other hand, when the coating is damaged, such as when the coating itself has defects or is scratched, the corrosive liquid will directly reach the surface of the metal substrate such as the magnesium substrate, and at this time, ASP and silicate ions are released, which form chelates and precipitates with the magnesium ions generated by magnesium corrosion, and synergistically achieve self-healing of the coating, and the coating returns to an intact state and continues to play the role of protecting the substrate. In view of the good biocompatibility of ASP and silicate, the LDH coating co-intercalated with ASP and silicate ions in the present invention is particularly suitable for corrosion protection of medical materials.
[0042] In addition, the present invention also further verifies that the self-healing protective coating on the surface of the magnesium-based material of the present invention has good biocompatibility through the good cell attachment and spreading of osteoblasts on the surface of the self-healing protective coating on the surface of the magnesium-based material.
[0043] Compared with the prior art, the present invention has the following advantages:
[0044] (1) The present invention adopts an innovative design of organic and inorganic ion co-intercalation LDH coating, which enables the coating to quickly and effectively repair itself after physical damage and chemical erosion, thereby reducing maintenance costs and improving material reliability;
[0045] (2) The protective coating and preparation method of the present invention not only greatly improve the corrosion resistance of magnesium-based materials (such as magnesium, magnesium alloys, magnesium-containing porous materials, magnesium-containing porous materials, materials treated with magnesium surface, materials treated with magnesium alloy surface, materials treated with magnesium porous materials, or materials treated with magnesium alloy porous materials, etc.), but also provide the possibility for application in high-requirement fields such as medical implant materials;
[0046] (3) In general, the present invention achieves more efficient and economical long-term protection of the surface of magnesium-based materials through the organic-inorganic ion co-intercalation LDH coating with good biocompatibility. This coating not only has broad application prospects in the field of medical implant materials, but is also suitable for high-end industrial fields such as aerospace, automobiles, and electronic information. It provides a new material protection strategy and is expected to lead a new trend in material protection technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0048] Figure 1 This is a surface morphology image of the sample prepared in Example 1 under a scanning electron microscope;
[0049] Figure 2 This is a cross-sectional view of the sample prepared in Example 1 under a scanning electron microscope;
[0050] Figure 3 XRD patterns of the LDH coating (AZ / L) prepared in Comparative Example 1, the LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating modified sample (AZ / LS) with silicate ion intercalation prepared in Comparative Example 3, the coating modified sample (AZ / LAS) prepared in Example 1, and the substrate sample;
[0051] Figure 4 The polarization curve results of the samples prepared in Example 1 and Comparative Examples 1 to 3 in artificial simulated body fluid at 37° C., wherein AZ / L is the LDH coating prepared in Comparative Example 1, AZ / LA is the LDH coating modified sample with ASP ion intercalation prepared in Comparative Example 2, AZ / LS is the LDH coating modified sample with silicate ion intercalation prepared in Comparative Example 3, and AZ / LAS is the coating modified sample prepared in Example 1;
[0052] Figure 5The graphs show the results of mouse preosteoblast adhesion on the surfaces of samples prepared in Example 1 and Comparative Examples 1 to 3, wherein (a) substrate, (b) LDH coating AZ / L prepared in Comparative Example 1, (c) LDH coating modified sample AZ / LA with ASP ion intercalation prepared in Comparative Example 2, (d) LDH coating modified sample AZ / LS with silicate ion intercalation prepared in Comparative Example 3, (e) coating modified sample AZ / LAS prepared in Example 1, and (f) statistical results of the number of adhered cells. DETAILED DESCRIPTION
[0053] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0054] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.
[0055] Unless otherwise specified, the terms used in the following implementation methods and examples generally have the meanings commonly understood by those of ordinary skill in the art.
[0056] Part I Surface Protective Coating of Magnesium-based Materials and Its Preparation Method
[0057] Example 1
[0058] The method for preparing the protective coating on the surface of the magnesium-based material provided in this embodiment comprises the following steps:
[0059] (1) Pretreatment of AZ31B magnesium alloy substrate;
[0060] A 10 mm × 10 mm × 10 mm AZ31B magnesium alloy sample was polished with 500#, 1000#, and 2000# sandpapers in sequence, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0061] (2) Preparation of ASP ion-intercalated LDH coating;
[0062] Under nitrogen protection, a deionized water solution of 60 mmol / L Mg(NO3)2·6H2O, 20 mmol / L A1(NO3)3·9H2O and 6.6 mmol / L aspartic acid ASP was prepared, and then the pH of the solution was adjusted to 12 with 2 mol / L NaOH to obtain a reaction solution;
[0063] The AZ31B magnesium alloy substrate pretreated in step (1) and the reaction solution were placed in a hydrothermal reactor and reacted at 120° C. for 15 hours to obtain an ASP ion-intercalated LDH coating on the surface of the AZ31B magnesium alloy.
[0064] (3) Preparation of LDH coatings co-intercalated with ASP and silicate ions;
[0065] A 50 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the LDH coating modified magnesium alloy sample with ASP ion intercalation obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 90°C for 2 hours to obtain an LDH coating (AZ / LAS) with ASP and silicate ions co-intercalated on the surface of the AZ31B magnesium alloy.
[0066] Example 2
[0067] The method for preparing the protective coating on the surface of the magnesium-based material provided in this embodiment comprises the following steps:
[0068] (1) Pretreatment of pure magnesium substrate;
[0069] A 10 mm × 10 mm × 10 mm pure magnesium sample was polished with 500#, 1000#, and 2000# sandpapers in turn, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0070] (2) Preparation of ASP ion-intercalated LDH coating;
[0071] Under nitrogen protection, a deionized water solution of 60 mmol / L Mg(NO3)2·6H2O, 20 mmol / L A1(NO3)3·9H2O and 16 mmol / L ASP was prepared, and then the pH of the solution was adjusted to 10 with 2 mol / L NaOH to obtain a reaction solution;
[0072] The magnesium substrate pretreated in step (1) and the reaction solution are placed in a hydrothermal reactor and reacted at 120° C. for 15 hours to obtain an ASP ion-intercalated LDH coating on the magnesium surface.
[0073] (3) Preparation of LDH coatings co-intercalated with ASP and silicate ions;
[0074] A 50 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the ASP ion intercalated LDH coating-modified magnesium sample obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 90°C for 2 hours to obtain an LDH coating co-intercalated with ASP and silicate ions on the surface of the pure magnesium substrate.
[0075] Example 3
[0076] The method for preparing the protective coating on the surface of the magnesium-based material provided in this embodiment comprises the following steps:
[0077] (1) Pretreatment of AZ31B magnesium alloy substrate;
[0078] A 10 mm × 10 mm × 10 mm AZ31B magnesium alloy sample was polished with 500#, 1000#, and 2000# sandpapers in sequence, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0079] (2) Preparation of ASP ion-intercalated LDH coating;
[0080] Under nitrogen protection, a deionized water solution of 60 mmol / L Mg(NO3)2·6H2O, 20 mmol / L A1(NO3)3·9H2O and 6.6 mmol / L ASP was prepared, and then the pH of the solution was adjusted to 12 with 2 mol / L NaOH to obtain a reaction solution;
[0081] The AZ31B magnesium alloy substrate pretreated in step (1) and the reaction solution are placed in a hydrothermal reactor and reacted at 140° C. for 12 hours to obtain an ASP ion-intercalated LDH coating on the surface of the magnesium alloy.
[0082] (3) Preparation of LDH coating co-intercalated with ASP and silicate ions.
[0083] A 50 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the AZ31B magnesium alloy sample modified with the LDH coating intercalated with ASP ions obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 90°C for 2 hours to obtain an LDH coating co-intercalated with ASP and silicate ions on the surface of the AZ31B magnesium alloy.
[0084] Example 4
[0085] The method for preparing the protective coating on the surface of the magnesium-based material provided in this embodiment comprises the following steps:
[0086] (1) Pretreatment of AZ31B magnesium alloy substrate;
[0087] A 10 mm × 10 mm × 10 mm AZ31B magnesium alloy sample was polished with 500#, 1000#, and 2000# sandpapers in sequence, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0088] (2) Preparation of ASP ion-intercalated LDH coating;
[0089] Under nitrogen protection, a deionized water solution of 60 mmol / L Zn(NO3)2·6H2O, 20 mmol / L A1(NO3)3·9H2O and 6.6 mmol / L ASP was prepared, and then the pH of the solution was adjusted to 12 with 2 mol / L NaOH to obtain a reaction solution;
[0090] The magnesium alloy substrate pretreated in step (1) and the reaction solution are placed in a hydrothermal reactor and reacted at 120° C. for 15 hours to obtain an ASP ion-intercalated LDH coating on the surface of the magnesium alloy.
[0091] (3) Preparation of LDH coating co-intercalated with ASP and silicate ions.
[0092] A 50 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the AZ31B magnesium alloy sample modified with the LDH coating intercalated with ASP ions obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 80°C for 4 hours to obtain an LDH coating co-intercalated with ASP and silicate ions on the surface of the AZ31B magnesium alloy.
[0093] Example 5
[0094] The method for preparing the protective coating on the surface of the magnesium-based material provided in this embodiment comprises the following steps:
[0095] (1) Pretreatment of AZ31B magnesium alloy substrate;
[0096] A 10 mm × 10 mm × 10 mm AZ31B magnesium alloy sample was polished with 500#, 1000#, and 2000# sandpapers in sequence, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0097] (2) Preparation of ASP ion-intercalated LDH coating;
[0098] Under nitrogen protection, a deionized water solution of 45 mmol / L Mg(NO3)2·6H2O, 15 mmol / L Fe(NO3)3·9H2O and 2 mmol / L sodium aspartate was prepared, and then the pH of the solution was adjusted to 11 with 2 mol / L NaOH to obtain a reaction solution;
[0099] The AZ31B magnesium alloy substrate pretreated in step (1) and the reaction solution were placed in a hydrothermal reactor and reacted at 110° C. for 25 hours to obtain an ASP ion-intercalated LDH coating on the surface of the magnesium alloy.
[0100] (3) Preparation of LDH coating co-intercalated with ASP and silicate ions.
[0101] A 35 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the LDH coating modified magnesium alloy sample with ASP ion intercalation obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 60°C for 8 hours to obtain an LDH coating with ASP ions and silicate co-intercalation on the surface of the AZ31B magnesium alloy.
[0102] Example 6
[0103] The method for preparing the protective coating with self-healing ability provided in this embodiment comprises the following steps:
[0104] (1) Pretreatment of pure magnesium substrate;
[0105] A 10 mm × 10 mm × 10 mm AZ31B magnesium alloy sample was polished with 500#, 1000#, and 2000# sandpapers in sequence, ultrasonicated in anhydrous ethanol for 10 minutes, and blown dry.
[0106] (2) Preparation of ASP ion-intercalated LDH coating;
[0107] Under nitrogen protection, a deionized water solution of 120 mmol / L Cu(NO3)2·3H2O, 40 mmol / L A1(NO3)3·9H2O and 25 mmol / L potassium aspartate was prepared, and then the pH of the solution was adjusted to 12 with 2 mol / L NaOH to obtain a reaction solution;
[0108] The magnesium substrate pretreated in step (1) and the reaction solution are placed in a hydrothermal reactor and reacted at 150° C. for 5 hours to obtain an ASP ion-intercalated LDH coating on the magnesium surface.
[0109] (3) Preparation of LDH coatings co-intercalated with ASP and silicate ions;
[0110] A 150 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the ASP ion intercalated LDH coating modified magnesium sample obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 60°C for 8 hours to obtain an LDH coating co-intercalated with ASP and silicate ions on the surface of the pure magnesium substrate.
[0111] Comparative Example 1
[0112] Compared with Example 1, Comparative Example 1 is different in that:
[0113] In step (2), ASP is not added, and step (3) is not performed. In step (2), an LDH coating (AZ / L) is obtained on the surface of the AZ31B magnesium alloy.
[0114] Comparative Example 2
[0115] Compared with Example 1, Comparative Example 1 is different in that:
[0116] The method does not contain step (3), in which a LDH coating modified sample (AZ / LA) with ASP ion intercalation is obtained on the surface of AZ31B magnesium alloy in step (2).
[0117] Comparative Example 3
[0118] Compared with Example 1, the difference is:
[0119] In step (2), ASP is not added, and in step (3), a silicate-intercalated LDH coating (AZ / LS) is obtained on the surface of the AZ31B magnesium alloy.
[0120] Figure 1 This is the surface morphology of the AZ / LAS sample prepared in Example 1 under a scanning electron microscope. The surface coatings of the AZ / L, AZ / LA and AZ / LS samples in Comparative Examples 1 to 3 all show similar morphologies, indicating that ion intercalation does not change the overall morphology. Different types of LDH coatings grow uniformly on the magnesium alloy substrate as a whole, showing a typical lamellar structure.
[0121] Figure 2 This is a cross-sectional view of the AZ / LAS sample prepared in Example 1 under a scanning electron microscope. Figure 2 It can be seen that there are no obvious cracks or defects between the coating and the magnesium alloy substrate, and the bonding is firm.
[0122] The XRD patterns of the LDH coating modified sample (AZ / L) prepared in Comparative Example 1, the LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating modified sample (AZ / LS) with silicate ion intercalation prepared in Comparative Example 3, and the LDH coating modified sample (AZ / LAS) with ASP and silicate ion co-intercalation prepared in Example 1 are shown in FIG. Figure 3 shown.
[0123] from Figure 3 It can be seen that the LDH coating modified sample (AZ / L) prepared in Comparative Example 1, the LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating modified sample (AZ / LS) with silicate ion intercalation prepared in Comparative Example 3 and the LDH coating modified sample (AZ / LAS) with ASP and silicate ion co-intercalation prepared in Example 1 all show the (003) characteristic diffraction peak of LDH.
[0124] The 003 peak position of AZ / LA (11.52°) is shifted to the left relative to the 003 peak position of AZ / L (11.61°). This is because the ASP ion radius is larger than the nitrate ion radius. From the Bragg formula, it can be seen that when the ion radius is larger, the characteristic diffraction peak value is smaller; since the silicate ion radius is between the nitrate and ASP ion radii, the 003 peak of AZ / LS shifts to 11.60°; the introduction of silicate causes the characteristic diffraction peak position of AZ / LAS to shift further to a lower angle, to 11.24°. Therefore, it can be seen that the hydrotalcite coating co-intercalated with aspartic acid and silicate is successfully prepared on the magnesium alloy substrate. Compared with Example 1, ASP was not added in step (2) of the sample of Comparative Example 1, and the LDH coating intercalated with ASP ions could not be prepared.
[0125] Comparative Example 4
[0126] Compared with Example 1, the difference is:
[0127] In step (2), the pH of the solution is adjusted to 8 using 2 mol / L NaOH to obtain a reaction solution. The remaining steps are the same as in Example 1. In step (3), an LDH coating of ASP and silicate ions co-intercalated is obtained on the surface of the AZ31B magnesium alloy.
[0128] Through the test of Comparative Example 4, it was found that if the pH value of the hydrothermal reaction solution is lower than 9, due to the activeness of magnesium, corrosion will occur on the surface of the magnesium-based material, causing rapid dissolution of magnesium, and it will be impossible to form a coating with good coverage and stability, or even no coating can be formed.
[0129] Similarly, when the pH value is greater than 13, a large amount of powdery precipitates will form on the surface of the base material, and it is impossible to form a uniform coating with good adhesion.
[0130] Comparative Example 5
[0131] Compared with Example 1, the difference is:
[0132] In step (2), the AZ31B magnesium alloy substrate pretreated in step (1) and the reaction solution are placed in a hydrothermal reactor and reacted at 80° C. for 15 hours. The remaining steps are the same as in Example 1. In step (3), an LDH coating of ASP and silicate ions co-intercalated is obtained on the surface of the AZ31B magnesium alloy.
[0133] The experiment of Comparative Example 5 found that if the hydrothermal temperature is lower than 100°C, the following effects may occur:
[0134] 1) Reduced reaction rate: A lower hydrothermal temperature will slow down the deposition reaction rate of LDH, thereby affecting the growth rate and uniformity of the coating. Under low temperature conditions, a thinner coating may form on the surface of the magnesium alloy, and the quality of the coating may not be as dense and uniform as at higher temperatures.
[0135] 2) Poor crystal structure: When the hydrothermal temperature is low, the crystallinity of the LDH crystals may be poor, and the formed LDH coating is not dense enough, which may affect the mechanical strength, corrosion resistance and adhesion of the coating to the substrate.
[0136] Comparative Example 6
[0137] Compared with Example 1, the difference is:
[0138] (3) Preparation of LDH coatings co-intercalated with ASP and silicate ions;
[0139] A 50 mmol / L Na2SiO3·9H2O deionized water solution was prepared, and the ASP ion intercalated LDH coating modified magnesium alloy sample obtained in step (2) and the prepared Na2SiO3 aqueous solution were placed in a hydrothermal reactor and reacted at 40°C for 2 hours to obtain an LDH coating co-intercalated with ASP and silicate ions on the surface of the AZ31B magnesium alloy.
[0140] Through the test of Comparative Example 6, it was found that when the ion exchange temperature was lower than 50°C, the following phenomenon would be aggravated:
[0141] 1) Reaction rate reduction effect: The rate of ion exchange reaction will be significantly reduced. Ion exchange usually requires a certain temperature to provide sufficient energy to drive ions from the solution to the substrate surface. When the temperature is too low, the diffusion rate of ions in the solution is slow, resulting in lower reaction efficiency and slower coating formation.
[0142] 2) Incomplete intercalation or structural instability effects: The intercalated ions in the solution may not be able to fully enter the LDH interlayer, resulting in an uneven coating composition or lack of expected ion intercalation. Especially for those coatings that require the insertion of silicate ions, low temperature may make the ion intercalation process incomplete.
[0143] It is found from the experiments of Comparative Examples 4-6 that when the pH value and temperature of the hydrothermal reaction and the ion exchange reaction temperature are not within the range of the present invention, the quality of the formed coating is very poor.
[0144] Part II Protective coating with self-healing ability and preparation method thereof
[0145] 1. Corrosion resistance test of each sample
[0146] The LDH coating (AZ / L) prepared in Comparative Example 1, the modified LDH coating sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating with silicate intercalation prepared in Comparative Example 3 (AZ / LS), the modified coating sample (AZ / LAS) prepared in Example 1 and the substrate sample were subjected to corrosion resistance test in artificial simulated body fluid at 37°C. The polarization curve results of each sample in artificial simulated body fluid at 37°C are shown in the figure. Figure 4 shown.
[0147] from Figure 4 It can be seen that the corrosion current density of AZ31B magnesium alloy matrix in simulated body fluid is 1.50×10 -4 A.cm -2 , which is the highest among all samples, indicating that the AZ31B magnesium alloy matrix is very susceptible to corrosion. This is because of its high electrochemical activity, the corrosion products formed cannot provide effective protection, and corrosion occurs rapidly in simulated body fluids.
[0148] Compared with the AZ31B substrate, the corrosion current density of the LDH coating sample (AZ / L) prepared in Comparative Example 1 decreased by nearly 2 orders of magnitude to 3.24×10 -6 A cm -2 , which is much lower than the value of AZ31B matrix sample, and the degradation is significantly inhibited.
[0149] Compared with the AZ31B substrate, the corrosion current density of the LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2 is further reduced, which is attributed to the active sites of the polar groups of the ASP ions released from the LDH interlayer, which interact with the magnesium ions and can be effectively adsorbed on the magnesium-based material to form a metal chelate, so that the coating self-heals and provides good corrosion protection for the magnesium substrate.
[0150] It is worth noting that the corrosion current density of the modified sample (AZ / LAS) of the LDH coating with ASP and silicate ions co-intercalated prepared in Example 1 is significantly lower than the corrosion current density value of the modified sample (AZ / LA) of the LDH coating with ASP ions intercalated prepared in Comparative Example 2 and the corrosion current density value of the modified sample (AZ / LS) of the LDH coating with silicate intercalated in Comparative Example 3. This may be due to the silicate ions released from the LDH coating and the magnesium ions dissolved from the matrix forming an insoluble magnesium silicate precipitate covering the corrosion site, further preventing the occurrence of corrosion. ASP and silicate ions play a synergistic role in corrosion inhibition, forming a composite coating with high protective performance, effectively slowing down the degradation of the magnesium matrix. In addition, since ASP and silicon have good biocompatibility, such LDH coatings with ASP and silicate ions co-intercalated can not only be used in industrial environments such as the ocean, but also are suitable for corrosion protection of medical materials.
[0151] 2. Mouse preosteoblast adhesion test on each sample surface
[0152] The LDH coating (AZ / L) prepared in Comparative Example 1, the modified LDH coating sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating (AZ / LS) with silicate intercalation prepared in Comparative Example 3, the modified coating sample (AZ / LAS) prepared in Example 1, and the AZ31B matrix sample were disinfected with 75% ethanol and placed in a 24-well cell culture plate, and 50,000 MC3T3-E1 mouse preosteoblasts were added to the above sample wells. After 12 hours of co-culture, the cells were first fixed with 4% paraformaldehyde for 15 minutes, then the cytoskeleton was stained with phalloidin for 40 minutes, and then the nucleus was stained with 4,6-diamidino-2-phenylindole for 5 minutes. Finally, the morphology and number of cells on the surface of the sample were observed under a fluorescence microscope, and statistical calculations were performed.
[0153] The results of mouse preosteoblast adhesion on the surfaces of the LDH coating (AZ / L) prepared in Comparative Example 1, the LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in Comparative Example 2, the LDH coating modified sample (AZ / LS) with silicate ion intercalation prepared in Comparative Example 3, the coating modified sample (AZ / LAS) prepared in Example 1 and the AZ31B substrate sample are shown in FIG. Figure 5 As shown, (a) AZ31B substrate sample, (b) LDH coating prepared in comparative example 1 (AZ / L), (c) LDH coating modified sample (AZ / LA) with ASP ion intercalation prepared in comparative example 2, (d) LDH coating modified sample (AZ / LS) with silicate ion intercalation prepared in comparative example 3, (e) coating modified sample (AZ / LAS) prepared in example 1, and (f) statistical results of the number of adhered cells.
[0154] from Figure 5 It can be seen that after the cells were cultured on the sample surface for 12 hours, the cells on the substrate sample were irregular in shape, with a small spreading area and a cell number of 37±4. In contrast, the number of cells on the LDH coating modified sample (AZ / L), the LDH coating modified sample intercalated with aspartic acid (AZ / LA) and the LDH coating modified sample intercalated with silicate ions (AZ / LS) increased, the cell spreading was good, and cell pseudopodia could be clearly observed. The number of cells on the sample surface was 47±13, 54±2 and 45±7, respectively. The number of cells on the surface of the LDH coating modified sample co-intercalated with aspartic acid and silicate (AZ / LAS) was the highest, reaching 85±6, and the spreading was the best, showing the best cell attachment and spreading behavior.
[0155] ASP is widely present in nature and participates in many life processes. It has good biocompatibility and provides a non-toxic repair substance for the coating. Silicon is one of the essential trace elements for the formation of normal human bone tissue, cartilage tissue, and connective tissue. It participates in the physiological process of regulating bone formation and bone calcification and plays an important role in bone metabolism. It can be seen that ASP and silicon have good biocompatibility and are expected to play a certain role in promoting bone formation. This type of LDH coating co-intercalated with ASP and silicate ions is not only suitable for medical materials with good biocompatibility, but also suitable for corrosion protection of medical materials.
[0156] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing a self-healing protective coating on the surface of a magnesium-based material, characterized in that: The following steps are involved: (1) Surface pretreatment of magnesium-based materials; (2) Preparation of LDH coating with organic corrosion inhibitor intercalation: Under a protective atmosphere, preparing an aqueous solution of a divalent metal ion salt, a trivalent metal ion salt and an organic corrosion inhibitor, and adjusting the pH to obtain a reaction solution; The magnesium-based material pretreated in step (1) and the reaction solution are placed in a hydrothermal reaction vessel to perform a hydrothermal reaction, thereby obtaining an organic corrosion inhibitor intercalated LDH coating on the surface of the magnesium-based material; (3) Preparation of LDH coating with co-intercalation of organic and inorganic corrosion inhibitors: Preparing an aqueous solution of an inorganic corrosion inhibitor; The magnesium-based material with the LDH coating intercalated with an organic corrosion inhibitor obtained in step (2) is immersed in the aqueous solution of the inorganic corrosion inhibitor to carry out an ion exchange reaction, thereby obtaining an LDH self-healing protective coating intercalated with an organic corrosion inhibitor and an inorganic corrosion inhibitor on the surface of the magnesium-based material.
2. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: The magnesium-based material described in step (1) is magnesium, magnesium alloy, magnesium-containing porous material, magnesium-containing porous material, material surface-treated with magnesium, material surface-treated with magnesium alloy, material surface-treated with magnesium porous material, or material surface-treated with magnesium alloy porous material; The surface pretreatment of the magnesium-based material described in step (1) includes: grinding the magnesium-based material to remove surface oxides and impurities, and then cleaning and drying it.
3. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: In step (2), the divalent metal ion salt is one or more of magnesium nitrate, zinc nitrate and copper nitrate; the concentration of the divalent metal ion salt is 30 to 120 mmol / L; the trivalent metal ion salt is one or two of aluminum nitrate and iron nitrate; the concentration of the trivalent metal ion salt is 10 to 40 mmol / L.
4. The method for preparing a self-healing protective coating on a magnesium-based material surface according to claim 1, characterized in that: The organic corrosion inhibitor in step (2) is one or more of aspartic acid, sodium aspartate and potassium aspartate, and the concentration of the organic corrosion inhibitor is 0.6-30 mmol / L.
5. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: The protective atmosphere in step (2) is one or more of nitrogen, argon and helium; and the pH in step (2) is adjusted to 9-13.
6. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 100 to 160° C. and the time is 1 to 30 hours.
7. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: The inorganic corrosion inhibitor in step (3) is sodium silicate, and the concentration of the inorganic corrosion inhibitor aqueous solution is 15 to 150 mmol / L.
8. The method for preparing a self-healing protective coating on the surface of a magnesium-based material according to claim 1, characterized in that: The temperature during the ion exchange reaction in step (3) is 50-100° C. and the time is 1-10 hours.
9. A self-healing protective coating on the surface of a magnesium-based material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the self-healing protective coating on the surface of a magnesium-based material according to claim 9 in the preparation of corrosion protection materials or biocompatible materials.
Citation Information
Patent Citations
Method for enhancing corrosion resistance of LDH (Layered Double Hydroxide) coating layer on surface of magnesium alloy
CN108330472A
Preparation method of amino acid ion intercalated ZnAl-LDHs film
CN112176338A
Corrosion-resistant aluminum alloy composite coating as well as preparation method and application thereof
CN114045479A
Method for sealing micropores of layered double-metal hydroxide coating on surface of magnesium alloy
CN115094418A
Corrosion-resistant hydrotalcite-like / metal composite coating as well as preparation method and application thereof
CN115110068A
Cited By
New application of organic-inorganic ion co-intercalation LDH composite coating modified by tannic acid-copper ion complex
CN121003734A